2023
DOI: 10.3390/plants12040692
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Regulation of Irrigation Management on Wheat Physiology, Grain Yield, and Quality

Abstract: Irrigation has been pivotal in sustaining wheat as a major food crop in the world and is increasingly important as an adaptation response to climate change. In the context of agricultural production responding to climate change, improved irrigation management plays a significant role in increasing water productivity (WP) and maintaining the sustainable development of water resources. Considering that wheat is a major crop cultivated in arid and semi-arid regions, which consumes high amounts of irrigation water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 134 publications
1
5
0
Order By: Relevance
“…These results mirror research indicating increased yield and water productivity with DI (Kharrou et al, 2011;Tasal and Pawar, 2015;Wakchaure et al, 2023). Studies by Ali et al (2007), Kabir et al (2009), El-Hwary and Yagoub (2011), and Si et al, 2023 observed significant irrigation impacts on wheat grain yield. Increased irrigations were linked to higher yields by El-Monoufi and Harb (1994), El-Barbary (1998), Ibrahim et al (2010) and Wu et al (2023).…”
Section: Effect Of Irrigation Schedules On Yield Componentssupporting
confidence: 79%
See 1 more Smart Citation
“…These results mirror research indicating increased yield and water productivity with DI (Kharrou et al, 2011;Tasal and Pawar, 2015;Wakchaure et al, 2023). Studies by Ali et al (2007), Kabir et al (2009), El-Hwary and Yagoub (2011), and Si et al, 2023 observed significant irrigation impacts on wheat grain yield. Increased irrigations were linked to higher yields by El-Monoufi and Harb (1994), El-Barbary (1998), Ibrahim et al (2010) and Wu et al (2023).…”
Section: Effect Of Irrigation Schedules On Yield Componentssupporting
confidence: 79%
“…The results indicate that as the irrigation depth increases, the WUE of wheat decreases linearly. This finding is supported by various researchers (Xiuwei et al, 2013;Patel and Rank, 2020;Yang et al, 2020;Si et al, 2023;Wang et al, 2023). The response of WUE (kg/ha-mm) to a depth of irrigation water applied (I in mm) can be described as an optimal irrigation scheduling method for wheat crops using CATD in the semi-arid conditions of western India.…”
Section: Relationship Between Irrigation Water Applied and Wuementioning
confidence: 59%
“…Except for genetic background, plant senescence is also affected by agronomic management In addition to genetic background, plant senescence is also affected by agronomic management. Appropriate irrigation scheduling will prolong the leaf photosynthetic duration and increase crop yields by alleviating drought stresses (Si et al, 2023). Acciaresi et al (2014) found that delayed leaf senescence at lower canopy levels was not associated with an increase in post-silking carbon (C) accumulation and may therefore be unproductive for maize under non-stressing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…During the maturing stage, wheat needs a temperature between 14 and 15 °C, and temperatures above 25 °C cause the weight of the grain to go down. But for grain filling, the temperature needs to be around 35.4 °C (Si et al, 2023).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%